The impact of transparency on foreign direct investment - Zdenek Drabek; Warren Payne (World Trade Organization (WTO), 2001)
Non-transparency is a term given in this paper to a set of government policies that increase the risk and uncertainty faced by economic actors foreign investors. This increase in risk and uncertainty stems from the presence of bribery and corruption, unstable economic policies, weak and poorly enforced property rights, and inefficient government institutions. Our empirical analysis shows that the degree of non-transparency is an important factor in a country's attractiveness to foreign investors. High levels of non-transparency can greatly retard the amount of foreign investment that a country might otherwise expect. The simulation exercise presented in the statistical part of this paper reveals that on average a country could expect 40 percent increase in FDI from a one point increase in their transparency ranking. Pari passu, non-transparent policies translate into lower levels of FDI and hence lower levels of welfare and efficiency in the host country's economy. A nation that takes steps to increase the degree of transparency in its policies and institutions could expect significant increases in the level of foreign investment into their country. This increased investment translates into more resources, which in turn increases social welfare and economic efficiency.
Keywords: F02; F13; F21; F23; M14; 330; Foreign direct investment; transparency; corruption; FDI modeling